Comfort rules for face masks among healthcare workers during COVID-19 spread - Maniaci, A.; Ferlito, S.; Bubbico, L.; Ledda, C.; Rapisarda, V.; Iannella, G.; La Mantia, I.; Grillo, C.; Vicini, C.; Privitera, E.; Coco, S.; Cammaroto, G.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The outbreak of Coronavirus disease 2019 (COVID-19) made imperative the use of protective devices as a source control tool. As there is no definite antiviral treatment and effective vaccine, the only efficient means of protecting and mitigating infectious contagion has been the use of personal protective equipment, especially by healthcare workers. However, masks affect the humidification process of inhaled air, possibly leading to a basal inflammatory state of the upper airways.Study design. This is a single-center observational study conducted at the University Hospital of Catania from April 1, 2020, to June 31, 2020.Methods. We analyzed the role of protective masks on the elimination of upper airways complaints in healthcare workers of the University Hospital of Catania. We evaluated 277 subjects through a selfadministered 17 item questionnaire based on respiratory, work performance and health-related quality of life domains.Results. A higher prevalence of nasal and ocular symptoms, perceived reduced work performance, difficulty in concentrating, and sleep disorders were found. After two weeks adhering to a list of good practices that we recommended, significant reversibility of the symptoms investigated and work performance enhancement were observed.Conclusions. Despite clinical complaints related to personal protective equipment, effective amelioration Background. The outbreak of Coronavirus disease 2019 (COVID-19) made imperative the use of protective devices as a source control tool. As there is no definite antiviral treatment and effective vaccine, the only efficient means of protecting and mitigating infectious contagion has been the use of personal protective equipment, especially by healthcare workers. However, masks affect the humidification process of inhaled air, possibly leading to a basal inflammatory state of the upper airways.Study design. This is a single-center observational study conducted at the University Hospital of Catania from April 1, 2020, to June 31, 2020.Methods. We analyzed the role of protective masks on the elimination of upper airways complaints in healthcare workers of the University Hospital of Catania. We evaluated 277 subjects through a selfadministered 17 item questionnaire based on respiratory, work performance and health-related quality of life domains.Results. A higher prevalence of nasal and ocular symptoms, perceived reduced work performance, difficulty in concentrating, and sleep disorders were found. After two weeks adhering to a list of good practices that we recommended, significant reversibility of the symptoms investigated and work performance enhancement were observed.Conclusions. Despite clinical complaints related to personal protective equipment, effective amelioration through usage rules is easily obtained. Given the essential use of protective masks, healthcare workers have to adhere to appropriate work and safety prevention rules.